AN ANALYSIS OF HUMOR IN J.M BARRIE’S PLAY “THE OLD LADY SHOWS HER MEDALS” ON EFL LITERATURE CLASS - Muhammad Nafi Annury (ETERNAL (English Teaching Journal), 2014)
People tend to find beauty in their life. They create such as painting, dance, music, literature and etc. As one of arts forms, literature is different from other forms of art. It is work writing. People read it for pleasure. They do it in order to know about human life, including its problems, customs, habits, ambition and desires.      The data of the study was taken by some following procedures: 1) quoting, means that the writer quoted the dialogue and the stage directions of the play which contains humorous expressions. 2) classifying, means that the writer classified the data into the five groups according to the types of humor such as “wit”, “sarcasm”, “satire”, “irony”, and “repartee”.     For the analysis the writer used aspects of drama or play to analyzing it. The aspects of play which is used in analyzing the data are synopsis, characterization (how the characters are described and how they behave), and the language (how the characters speak and how humor is reflected in the play). The writer attempted to understand the meaning of the play and how the expressions of humor employed in the play. He identified sentences that represent characters’ feeling and expressions.             Last but not least, the writer used descriptive analysis method. Since the descriptive method is used in the literal sense of describing situations or events. The writer used the descriptive analysis to report the result of the analysis from the data taken. In this case he described expressions of humor which are found in the play